Pengembangan Alat Obat Nyamuk Otomatis untuk Mengurangi Tingkat Penyebaran Penyakit Malaria - Cahyono, Yohan Ananda; Sahara, Siti; Farezan, Arsad Rifki Adhawi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The spread of malaria caused by mosquito bites remains a global health problem. To mitigate the spread of this disease, the development of automatic mosquito-repellent devices is one viable solution. This study aims to develop an automatic mosquito-repellent device that effectively controls the population of malaria-carrying mosquitoes. The research methodology includes the design and construction of the device, field trials, and data analysis. The research findings indicate that the automatic mosquito-repellent device significantly reduces the population of malaria-carrying mosquitoes in the trial area. Discussions on the implications of these findings for malaria control strategies and suggestions for further development of the device are also presented. This research is expected to contribute to global efforts to reduce the burden of malaria.